Bone Marrow Morphology: A Key Diagnostic Tool in Various Hematological and Non Hematological Disorders: Bone Marrow Morphology - Arif, Mizna; Arif, Sarah; Maab, Rafeeda; Shaikh, Huma (Pakistan Journal of Health Sciences, 2024)
Bone marrow morphology means microscopic examination of bone marrow cells and tissue samples obtained by aspirate and trephine biopsy. An invaluable tool for diagnosis of many hematological and non-hematological disorders, various types of cancer staging and metastases detection. Different kinds of anemia and leukemia can be accurately diagnosed and monitored. Objective: To check the spectrum of diseases which could be identified and diagnosed with the help of bone marrow morphology examination thus demonstrating its diagnostic utility and to check diagnostic concordance between aspirate and core biopsy. Methods: Cross sectional study with consecutive sampling technique conducted over period of one year. Samples of both Bone Marrow Aspiration (BMA) and trephine biopsy (BMB) were collected from all patients included in study after consent using standard protocols. Air dried smears were prepared from bone marrow aspiration samples while trephine biopsy tissues were processed by histopathological techniques. Routine staining such as Wright Giemsa stain, H and E stain and special cytochemistry were used to visualize the cellular architecture of bone marrow. Results: Out of 471 samples, males were predominant with the frequency of 63.9% and maximum patients (31.8%) were from the age group of 35-40 years. Most common clinical indication to conduct bone marrow examination was unexplained Cytopenia which accounted for 35.2% cases, followed by suspicion of Leukemia (28.5%). Malignant hematological disorders were more common as compared to benign disorders (64% vs 17.5%). Acute leukemia was the most commonly identified cancer with frequency of 27.6%. Conclusions: Bone marrow morphology till date remains low risk, economical, crucial diagnostic tool in especially in under resource country like Pakistan. It can guide physicians to plan proper and timely management of patients.